Towards Clinical Bioinformatics: Redux 2015 - Altman, R. B. (Yearbook of Medical Informatics, 2016)
In 2004, medical informatics as a scientific community recognized an emerging field of “clinical bioinformatics” that included work bringing bioinformatics data and knowledge into the clinic. In the intervening decade, “translational biomedical informatics” has emerged as the umbrella term for the work that brings together biological entities and clinical entities. The major challenges continue: understanding the clinical significance of basic ‘omics’ (and other) measurements, and communicating this to increasingly empowered patients/consumers who often have access to this information outside usual medical channels. It has become clear that basic molecular information must be combined with environmental and lifestyle data to fully define, predict, and manage health status..
Keywords: Clinical bioinformatics; translational biomedical informatics; direct-to-consumer genetics; consumer informatics